2014
DOI: 10.2196/jmir.3078
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Congruence of Crowdsourced Information With Official Government Data: The Case of Pediatric Clinics

Abstract: BackgroundHealth 2.0 is a benefit to society by helping patients acquire knowledge about health care by harnessing collective intelligence. However, any misleading information can directly affect patients’ choices of hospitals and drugs, and potentially exacerbate their health condition.ObjectiveThis study investigates the congruence between crowdsourced information and official government data in the health care domain and identifies the determinants of low congruence where it exists. In-line with infodemiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Although some contemporary studies address both the demand based and supply based approaches (Bragazzi, Dini, Toletone, Brigo & Durando, ; Bragazzi, Watad, et al., ; Brigo & Erro, ; Lampos, Yom‐Tov, Pebody & Cox, ; Nagar et al., ; Santos & Matos, ). The last group is categorised as ‘other studies’ in which no Web tools were used (Chen et al., ; Kim, Jung, Jung & Hur, ; Kind et al., ; Liu et al., ; Showghi & Williams, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some contemporary studies address both the demand based and supply based approaches (Bragazzi, Dini, Toletone, Brigo & Durando, ; Bragazzi, Watad, et al., ; Brigo & Erro, ; Lampos, Yom‐Tov, Pebody & Cox, ; Nagar et al., ; Santos & Matos, ). The last group is categorised as ‘other studies’ in which no Web tools were used (Chen et al., ; Kim, Jung, Jung & Hur, ; Kind et al., ; Liu et al., ; Showghi & Williams, ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on The United Nations’ country classification (United Nations, ), the findings indicated that 46 (82%) articles were related to developed countries, as shown in Table , while seven (12.5%) were related to developing countries (Chan, Ho & Lam, ; Chen et al., ; Kim et al., ; Liu et al., ; Ocampo, Chunara & Brownstein, ; Wang et al., ; Wong et al., ). Three demand based articles (5%) belong to Russia as a country in transition (Domnich et al., ; Zheluk, Quinn, Hercz & Gillespie, ; Zheluk, Quinn & Meylakhs, ).…”
Section: Resultsmentioning
confidence: 99%
“…The Kendall coefficient (W) [24][25][26][27][28][29] was used to assess the concordance among to judge the concordance. The significance level is set at 0.05.…”
Section: Task 4: Investigating the Features Of The Kendall Coefficienmentioning
confidence: 99%
“… 54 Indeed, there is some indication e-MH resources are not widely accessed by young people. 55 One potential difficulty may be related to what has been coined the ‘ technology push’ , whereby e-MH solutions are designed to fit available technology, rather than to meet the unmet needs and preferences of end-users. 56 Furthermore, research indicates poor uptake and ongoing use of e-MH interventions that have been implemented into healthcare settings within the general population.…”
Section: Introductionmentioning
confidence: 99%